NEW TRANSPORT MEDIUM FOR SHIPMENT OF CLINICAL SPECIMENS I. : Fecal Specimens - Cary, Sylvia G. (1964)
Cary, Sylvia G. (Walter Reed Army Institute of Research, Washington, D.C.), and Eugene B Blair. New transport medium for shipment of clinical specimens. I. Fecal specimens. J. Bacteriol. 88:96–98. 1964.—A new transport medium for the collection and shipment of clinical specimens is described. Preliminary studies indicate that, with initial fecal specimens, Salmonella and Shigella can be recovered for as long as 49 days, Vibrio comma for 22 days, and Pasteurella pestis for at least 75 days.